Preoperative risk score and in-hospital death following isolated myocardial revascularization surgery (Research, Society and Development, 2022)
Cardiovascular disease is the leading cause of death in Brazil. The risk of in-hospital death after coronary artery bypass grafting (CABG) can be assessed by identifying preoperative factors and quantified through scores. This investigation analyzed associated with mortality in the hospital phase after isolated CABG, to develop a preoperative risk score (PRS) for postoperative in-hospital death. This observational, retrospective, single-center study examined comorbidities and complementary exams of 9,826 patients who underwent isolated CABG between January 1, 1999 and December 31, 2017 were analyzed to identify their correlation with postoperative in-hospital death. A total of 9,826 patients were divided into the construction group (7,860; 80%) and validation group (1,966; 20%). The mean age of the patients was 62.43 years. Most patients were men (70.2%). Fifteen independently related factors were identified for hospital mortality. The final logistic model was calculated in the construction group with a C-statistic of 0.745 (95% confidence interval [CI], 0.720–0.770). In the validation group, the score was tested by obtaining an area under the receiver operating curve of 0.716 (95% [CI], 0.666–0.767). Death occurred in 489 patients (5%). The risk of death ranged from 1.2% in those considered to be low risk (PRS 211). The PRS score satisfactorily discriminated among patients who exhibited low, intermediate, high, and very high risk of death in the postoperative period. PRS could serve as an auxiliary tool in the preoperative period for surgical teams.